Analisis Manajemen Risiko pada Penyelenggaraan Ibadah Umrah di Arabia Tour and Travel Padang - Mohammad Daffa; Andis Febrian (Darul Yasin Al Sys, 2026)
Although risk management in financial institutions and e-commerce businesses has been widely studied, research that specifically discusses the implementation of risk management among Umrah travel organizers in West Sumatra from the perspective of sharia management remains limited. This study aims to analyze the implementation of risk management, identify obstacles, and examine the impact of risk management on the operations of Arabia Tour and Travel Padang from the perspective of sharia management. This study used a qualitative approach with data collection techniques through in-depth interviews, observation, and documentation involving ten informants consisting of the operational manager, employees, and pilgrims. Data were analyzed through the stages of data reduction, data display, and conclusion drawing. The results show that Arabia Tour and Travel Padang implements risk management in a structured manner through three stages, namely risk identification, analysis, and management. The strategies implemented include price locking, sharia insurance (takaful), a regulatory monitoring team, transportation crisis management, and double document verification. This finding confirms that the implementation of risk management at Arabia Tour and Travel Padang has integrated sharia values, namely amanah, siddiq, ta’awun, maslahah, and ihsan, thereby having a positive impact on financial stability and pilgrims’ trust. The conclusion of this study indicates that risk management in Umrah travel agencies has not only managerial-business dimensions but also spiritual and ethical dimensions that need to be integrated comprehensively. The implications of this study contribute to the development of sharia management studies and provide a practical basis for Umrah travel organizers in strengthening risk governance that is professional, ethical, and oriented toward the welfare of pilgrims.